PEMBENTUKAN AKHLAQUL KARIMAH DI MADRASAH ALIYAH SUMBER AGUNG KEMILING BANDAR LAMPUNG - Subni, Subni (STIT Pringsewu, 2018)
For teachers aqidah akhlak, implement good performance can simplify the process of formation of morality, so that learners are able to have the ability in the field of cognitive, psychomotor and affective. Formation of morals has been adhered to by teachers aqidah akhlak, but still there are violations committed by learners. This study aims to determine what factors are causing learners foul in school. Data obtained from this study is by observation, documentation and interview about the performance of teachers and learners. The field research is descriptive qualitative which is based on primary data, ie data obtained directly from the teacher aqidah akhlak and learners, and secondary data is data obtained indirectly, namely through media intermediaries or from other parties, such as principals and teachers' board another. The data obtained is then analyzed inductively, by way of identifying things that are special and then pulled into general conclusions. The results of this study showed that there were violations committed by students. This violation is caused by internal factors of learners themselves and the external factors are derived from the family, school and community.